Social and behavioral vulnerability, pregnancy, and negative mental health outcomes in the U.S. during the Covid-19 pandemic - Stephanie A. Godleski; Casey T. Harris; Kevin M. Fitzpatrick; Ammina Kothari (AIMS Press, 2022)
The novel coronavirus (Covid-19) pandemic has had a significant impact on the mental health of the general U.S. population. Extant literature has increasingly linked social vulnerabilities, risky behavior, and limited social and psychological resources to the growing mental health crisis during the virus's spread. The purpose of this study was to examine the impact of pertinent social vulnerabilities and subjective risk factors for both men and women on mental health (i.e., depression, anxiety, isolation) with a closer examination of the influence of pregnancy during the pandemic on mental health. The sample included 740,640 respondents participating in the U.S. Covid-19 Trends and Impact Survey that was deployed between February and March 2021. Descriptive statistics and ordinary least squares regression models are presented with a focus on the factors that shape negative mental health outcomes, particularly on the disparities between pregnant and non-pregnant women relative to men, but also subjective/perception factors (e.g., fear/worry) and social vulnerabilities. Results show that pregnant women were at significantly greater risk of negative mental health outcomes at this stage of the pandemic than either men or non-pregnant women. Overall, respondents who were younger, without children in the household, unemployed, worried generally about infection or their finances, or had ever tested positive for Covid were also more likely to report feelings of anxiety, isolation, and depression than their counterparts. Pregnant women may be especially vulnerable to depression, anxiety, and isolation during the pandemic and our findings suggest the importance of developing targeted mental health support for this sub-population.